Academic stress and its psychosocial and behavioral determinants in medical students: Findings from a cross-sectional study - Md Rizwanul Karim; S. A. Sazin Haque; Faiza Rumeen; Purna Aruneema (PLoS ONE, 2026)
Background Academic stress is a widespread challenge in medical education, with psychological, behavioral, and contextual factors contributing to it. This study estimated the prevalence of academic stress among Bangladeshi medical students and identified key psychosocial and behavioral predictors to guide targeted interventions. Methods A multicenter cross-sectional study (October–December 2022) used a stratified random sample of 1,072 undergraduate students from eight public medical colleges representing all administrative divisions of Bangladesh. Validated instruments measured academic stress (Academic Stress Scale, ASS-40), depressive symptoms (PHQ-9), anxiety (GAD-7), insomnia (ISI), internet addiction (IAT), self-esteem (RSES), and coping styles (SCSI). Analyses included descriptive statistics, chi-square and Mann–Whitney U tests, multivariable logistic regression to identify independent predictors, and structural equation modeling (SEM) and network analysis to explore direct and indirect pathways. Result Academic stress was reported by 47.5% of participants. In adjusted logistic regression models, moderate anxiety was associated with increased odds of academic stress (AOR = 3.95; 95% CI 1.98–7.90), and severe depression showed a markedly elevated association (AOR = 21.54; 95% CI 7.21–64.38). Behavioral factors were also influential: moderate-to-severe problematic internet use was strongly associated with academic stress (AOR = 17.78; 95% CI 9.66–32.72). Additional independent predictors included advanced academic year, higher monthly expenditure, and urban residence. Active problem-focused coping conferred modest protection against academic stress (AOR = 0.89; 95% CI 0.83–0.95). Structural equation modeling supported a model in which psychological distress exerted both direct effects on academic stress and indirect effects mediated by sleep disturbance and internet addiction, while network analysis identified depressive symptoms, insomnia, and internet addiction as central nodes within the stress network. Conclusions Nearly half of the sampled medical students experienced significant perceived academic stress. Interventions that integrate mental health services, sleep-hygiene promotion, responsible digital-use policies, and training in adaptive, problem-focused coping are recommended.